2015
DOI: 10.17795/ajehe-2698
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study on the Removal of Phenol From Aqueous Solution Using Organomodified Bentonite and Commercial Activated Carbon

Abstract: The potential of bentonite modified with cationic surfactant (CTAB-Bent) and commercial Activated Carbon (AC) for the removal of phenol removal was assessed. Batch kinetics and isotherm studies were carried out to evaluate the effects of contact time (t), phenol initial concentration (C 0 ), adsorbent dose (C ads ), and pH of the solutions. Kinetics and isotherm of the adsorption were also determined using the most frequent models. The results of the study showed that increasing C 0 could result in the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
(33 reference statements)
3
2
0
Order By: Relevance
“…Finally, Haseena et al [ 43 ] investigated the potential use of bentonite in eliminating ammonia from aqueous solutions. Based on the literature [ 44 ], we speculated that bentonite and zeolite could be used to remove phenols and metals from water, which was verified by the results. As noted above, the composite adsorbent BAZLSC can perform ion exchange and adsorption, since it contains bentonite, zeolite, limestone, shell, cement, and activated carbon [ 45 ].…”
Section: Resultssupporting
confidence: 63%
“…Finally, Haseena et al [ 43 ] investigated the potential use of bentonite in eliminating ammonia from aqueous solutions. Based on the literature [ 44 ], we speculated that bentonite and zeolite could be used to remove phenols and metals from water, which was verified by the results. As noted above, the composite adsorbent BAZLSC can perform ion exchange and adsorption, since it contains bentonite, zeolite, limestone, shell, cement, and activated carbon [ 45 ].…”
Section: Resultssupporting
confidence: 63%
“…The result is a reduction of pollutant adsorbed per unit mass of carbon. Mathematically speaking, the term C/(X/M) will decrease with the decrease of M, thus the ADC & AADC will be increased with a reduction of M. Similar trend was found by [6,19,21,[28][29][30] Fig. 7 and Table 1 show that the ADC & AADC is directly proportional with Co. Increase of Co will act on two direction, each of them will increase ADC & AADC.…”
Section: Applicability Of Adsorption Modelssupporting
confidence: 72%
“…A lot of researches had been conducted employing batch adsorption scheme using different adsorbents. The results of these researches indicated that adsorption capacity (ADC) is found to be increased with the increase of pollutant concentration [6,[17][18][19][20][21][22] and with the decrease of carbon dose (CD) [6,17,19]. It is also found that pollutant removal is directly proportional with the adsorbent dose and contact time [16,20,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, The TTB-Mt-1 with the positive charged surfaces could adsorb the pheolics with the negative charge when the pH of solution is higher than pk a . Similar results on the separation of phenolics by sugarcane bagasse (Elayadi et al 2021) and adsorption of phenol by CTB-bentonite (Leili et al 2015) reported the AE of phenolics from OMW was increased when the pH was increased from 2 to 12.…”
Section: Effect Of Phsupporting
confidence: 66%